STRUKTUR INSANG IKAN Ompok hypophthalmus (Bleeker 1846) DARI PERAIRAN SUNGAI SIAK KOTA PEKANBARU - Dwi Indrayani; Yusfiati '; Roza Elvyra (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This study aimed to observe the pathology of fish gill tissue Ompok hypophthalmus from Siak River around Siak I and Siak II bridge, Pekanbaru. The research was conducted from December 2013 to April 2014. The samples were prepared for histological observation using paraffin method and stained with Hematoxylin-Eosin (HE). Data were analyzed descriptively and quantitatively based on the histopathological evaluation and the value of the damage scoring. The results showed that the gill tissue structure of O.hypophthalmus fish changed. The damage in gill tissue found at Station I were 8,4% hyperplasia, 5,9% lamella fusion, 2,9% odema and 0,9% necrosis with total damage of gill tissue was 18,1%. Meanwhile, the damage in gill tissue found at Station II were 7,1% hyperplasia, 6,1% lamela fusion, 2,4% odema and 0,9% necrosis with total damage of gill tissue was 16,5%. The results of histopathological scoring below ≤25% indicated that the condition of the gill tissue was considered normal.